2006
DOI: 10.1021/ja0603453
|View full text |Cite
|
Sign up to set email alerts
|

C7and C9Carbon-Rich Bridges in Diruthenium Systems:  Synthesis, Spectroscopic, and Theoretical Investigations of Different Oxidation States

Abstract: Two methodologies of C-C bond formation to achieve organometallic complexes with 7 or 9 conjugated carbon atoms are described. A C7 annelated trans-[Cl(dppe)2Ru=C=C=C-CH=C(CH2)-C[triple bond]C-Ru(dppe)2Cl][X] (X = PF6, OTf) complex is obtained from the diyne trans-[Cl(dppe)2Ru-(C[triple bond]C)2-R] (R = H, SiMe3) in the presence of [FeCp2][PF6] or HOTf, and C7 or C9 complexes trans-[Cl(dppe)2Ru-(C[triple bond]C)n-C(CH3)=C(R1)-C(R2)=C=C=Ru(dppe)2Cl][X] (n = 1, 2; R1 = Me, Ph, R2 = H, Me; X = BF4, OTf) are forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
68
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 115 publications
4
68
0
Order By: Relevance
“…We chose this particular system because it was used in previous conductance measurements 22,23 as a monomer of chains -albeit with different anchor groups -where it was found that depending on the chain length either coherent transport or electron hopping is observed 22 . In addition spectroscopic and quantum chemical studies on similar Ru complexes [24][25][26][27][28] suggest that this molecular species offers the possibility to easily link two carbon-rich chains to each other for the formation of reversible redox systems [29][30][31] with distinct optical transition properties 32,33 , thereby serving as a starting point for the investigation of chains with multiple redox active centers 27 . In contrast to Ref.…”
Section: Introductionmentioning
confidence: 99%
“…We chose this particular system because it was used in previous conductance measurements 22,23 as a monomer of chains -albeit with different anchor groups -where it was found that depending on the chain length either coherent transport or electron hopping is observed 22 . In addition spectroscopic and quantum chemical studies on similar Ru complexes [24][25][26][27][28] suggest that this molecular species offers the possibility to easily link two carbon-rich chains to each other for the formation of reversible redox systems [29][30][31] with distinct optical transition properties 32,33 , thereby serving as a starting point for the investigation of chains with multiple redox active centers 27 . In contrast to Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Highly unsaturated, rigid -(C"C) n -and -(C@C) n -bridges offer an extended p-system and have been recognized as being particularly efficient in mediating electronic transfer [5][6][7][8][9][10]. In this context, a vast number of mono-and bimetallic complexes with polyynediyl or polyacetylene bridges have been extensively studied [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the decreasing of the DE 1/2 value from 0.53 V in n = 2, 0.38 V in n = 3 to 0.28 V in n = 4 indicates that the magnitude of Re 2+ -Re 2+ interaction is decreased significantly on the number of C"C moiety. Furthermore, complexes with an odd numbered carbon linear or cyclic bridge has been recently found to promote very efficient electronic communication between two [RuCl(dppe) 2 ] + metal centers [25].…”
Section: Introductionmentioning
confidence: 99%